Effect of Mulch Type on Plant Growth and Production Shallots (Allium Fistulusum L.) - Wa Ode Anti; Lisman Sonsoso; Samiati Samiati; Fifi Angrasari (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2021)
This research aimed to study the mulch's effect on the growth and yield of onion leaves plants. The research at held for three months, from June to September 2020. The research at Lasalepa village, Lasalepa District, Muna Regency, Southeast Sulawesi Province. The materials used in this study were scallion seeds, cow manure, rice straw mulch, reed mulch, corn litter mulch, and krinyuh mulch. The tools used consisted of a machete, hoe, tape measure, cheerful, bucket, raffia rope, scissors, sprayer, camera, digital scales, and writing instruments. The research was arranged base on randomized block design (RBD) consisting of 5 (five) treatment levels, namely without mulch as control (M0), rice straw mulch (M1), reed mulch (M2), corn litter mulch (M3) and krinyuh mulch (M4). Variable observed there was plants height (cm), number of leaves (strands), number of tillers, and production (g/ plant). All data were analyzed based on Analysis of Variance (ANOVA) at a 95% confidence level. The insignificant difference, followed by the Honestly Significant Different (HSD) test at a 95% confidence level. The research showed that the treatment of different types of mulch had a significant effect on plant height, number of leaves, number of tillers, and production. Krinyuh mulch type with a rate of 90 g plant-1 or 10 t ha-1 gave the best growth and production of scallions with an average production of 131.8 g plant-1 or 32.95 ha-1.